Décomposition de la forme « projet » - Vincent Beaubois (Appareil)
The notion of “project” is presented today as the specific regime of creative activity and as the temporal form of innovation. With a philosophy of design concerning “things” (mechanical) and “non-things” (digital), Vilém Flusser proposes an original reading of the history and epistemology of design practices. This reading goes precisely through this notion of “project” which acts as an attractor carrying in the same dynamic two distinct perspectives: the “existential project” thought as individual and social realization and transformation, and the “technological project” thought as process of innovation. The articulation of his philosophy of design and his reflection about post-history through this notion of “project” engages a critique of the “modern” thinking of technological development: design no longer acts as a process of “problem solving” improving our living conditions, but as the programming of “alternative worlds” in which our actions are molded. From this evolution of the understanding of design comes a decomposition of the temporal form embodied by the notion of “project”.